Mabadai
  • Member for 1 year, 9 months
  • Last seen more than 1 year ago
About

☒ B.Med.L.Sc

☐ B.Sc(CS)

Proof that 1 = 2:

a^2  = ab
a^2 - b^2 = ab - b^2
(a + b)(a - b) = b(a - b)
(a + b) = b
2b = b

Have you spotted the error on line 3? The rest is nonsense.

Badges
This user doesn’t have any gold badges yet.
This user doesn’t have any silver badges yet.
1
bronze badge
Top tags
-1
Score
1
Posts
100
Posts %
-1
Score
1
Posts
100
Posts %
-1
Score
1
Posts
100
Posts %
-1
Score
1
Posts
100
Posts %